Internal Carbon of Chemical Molecules Play in Intermolecular Association Favoring Stability - Rajasekaran, Ekambaram; Meenal , Rajasekaran (Research Aspects in Chemical and Materials Sciences Vol. 5, 2022)
Internal carbon of all bio molecules interactively plays a crucial role in association and function but little is known in the literature and all. Other parameters like coexistence and all needed to be studied thoroughly for survival and analysis. Best way to deal with this new developments needed to be analyzed at the bottom of research where in chemicals can be crucial in design and survival where amino acids may be important in protein research. Additional understanding must be adequate enough to deal with future technology development for existence of nature. Here we have developed a concept for future technology that can coexist in nature. Analysis of minimum component molecular system is taken here for study and all. Analysis proves that adequacy is sufficient to explain all unnatural phenomena of boiling and melting point in chemical system of interest. Adequacy is the key point to deal with abnormal values associated with certain compounds and all. Understandably the internal one is going to be crucial for any such deviation and all. Analysis provides enough insight into the existence and all. Probably dealing can be reached to any system of interest where carbon going to be major player and all. Internal one is the system of interest for future technology development and all. Developments needed to be continued in this direction for futuristic development of robo like structure that will walk away with existence of internal matter and all. Arrangements are to be made available for such a development and all.